Translating technical metaphors from English into Malay: possibilities (and challenges) - Sharmini, Abdullah (Universiti Malaysia Perlis, 2014)
Symposium of International Language & Knowledge (SiLK 2014), 14th-16th Feb 2014 was held at Hydro Hotel, Penang organized by Centre for International Languages, Universiti Malaysia Perlis.